The Black Burnished Type 18 Bowl and the Fifth Century - James Gerrard (Internet Archaeology, 2016)
This article discusses a late Roman Black Burnished form known as the Type 18 bowl. The lateness of this form was first discussed in 2004 but new discoveries have continued to reinforce the probably late fourth to early fifth century date assigned to this vessel. Imitations in other fabrics are also beginning to be identified with one such vessel found in association with early Anglo-Saxon pottery.